Investigating Young Learner’s Oral Fluency through Language Immersion Programs in Home Country: A Case Study - Rodiyah; Sabilah, Fardini; Hartiningsih, Sri (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
This study investigates language immersion programs run by first-grader's English language student. By conceiving the concept of immersion in relation to preservice and in-service teaching approaches that mirror natural settings, we want to explore how first grader who participate in immersion programs improve her English proficiency outside of the classroom. We examined how an Indonesian female elementary school student who was studying English acquired her oral fluency through immersion inside and outside of the classroom setting and how her English proficiency has altered over time through a qualitative case study. The information was gathered through observation and in-depth interviews, and it was then thematically evaluated according to. Our investigation produced four main themes: (1) Place-Based Geography, (2) Person-Based Classification, (3) Types-Based immersion, and (4) Oral Production Fluency based Predictors and Assessment. These interconnected topics show a description of the students' English skills and confirm the progress they made during the immersion program. The results offer teacher educators sophisticated insight into the ways in which immersion programs are extended through extracurricular activities, the multimodal character of literacies, and chances for social responsiveness. Each of these insights is especially helpful for English language teachers. In conclusion, three communities namely the school, participants’ home, and English learning center help participant to develop her speaking fluency.